2000
DOI: 10.1155/2000/640501
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux and Asthma: Can the Paradox Be Explained?

Abstract: BACKGROUND AND OBJECTIVE:The reported effects of asthma on gastroesophageal reflux (GER), effects of GER on asthma and the effects of antireflux therapy on asthma are conflicting. The purpose of this paper is to review the evidence for a relationship between the two conditions.DESIGN:A search of the MEDLINE 1966 to 1999 database, combining the terms GER and asthma, was used to identify studies of the effects of acid perfusion of the esophagus, the physiological equivalent of GER and the effects of both medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 100 publications
(111 reference statements)
0
6
0
3
Order By: Relevance
“…Obese individuals are generally sedentary, which may result in increased time spent indoors, thereby predisposing them to indoor air allergens, environmental tobacco smoke, and dust mite antigens. Obesity also predisposes to gastro-oesophageal reflux disease, which may induce asthmatic symptoms [35]. Given the current concern regarding obesity as a public health problem in the USA, a more detailed evaluation of this association is definitely warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals are generally sedentary, which may result in increased time spent indoors, thereby predisposing them to indoor air allergens, environmental tobacco smoke, and dust mite antigens. Obesity also predisposes to gastro-oesophageal reflux disease, which may induce asthmatic symptoms [35]. Given the current concern regarding obesity as a public health problem in the USA, a more detailed evaluation of this association is definitely warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The association between asthma and GERD has been well established in clinical studies, and several causal relationships have been proposed, including microaspiration, vagal reflex, and airway hyperresponsiveness. 61,62 There are some possible explanations for the small improvement with PPIs observed in our meta-analysis. First, the primary mechanism of action of PPI therapy is acid suppression.…”
mentioning
confidence: 91%
“…(7) One group of researchers suggested that gastroesophageal reflux causes asthma symptoms but does not significantly affect the pulmonary function. (18) The authors attributed the asthma-like symptoms to the retrosternal discomfort that increases minute ventilation and the respiratory sensation. This contradicts the findings of another study which showed a drop in FEV 1 at up to 90 minutes after instillation of hydrochloric acid in the esophagus of asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%